2023
DOI: 10.1002/wrna.1829
|View full text |Cite
|
Sign up to set email alerts
|

RNA m6A modifications regulate crosstalk between tumor metabolism and immunity

Jinghua Gu,
Huake Cao,
Xiaoli Chen
et al.

Abstract: In recent years, m6A modifications in RNA transcripts have arisen as a hot topic in cancer research. Indeed, a number of independent studies have elaborated that the m6A modification impacts the behavior of tumor cells and tumor‐infiltrating immune cells, altering tumor cell metabolism along with the differentiation and functional activity of immune cells. This review elaborates on the links between RNA m6A modifications, tumor cell metabolism, and immune cell behavior, discussing this topic from the viewpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 247 publications
0
1
0
Order By: Relevance
“…Another study indicated that METTL14 interacts with the microprocessor protein DGCR8, promotes the processing and maturation of pri-miRNA126, and inhibits the metastasis of liver cancer[ 17 ]. Furthermore, m6A modification participates in the various aspects of tumor development, such as immunity, metabolism, and tumor stem cells’ self-renewal[ 18 , 19 ], emerging as an important molecular biomarker in tumor initiation and development. m6A dysregulation exerts multiple regulatory effects in GC[ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that METTL14 interacts with the microprocessor protein DGCR8, promotes the processing and maturation of pri-miRNA126, and inhibits the metastasis of liver cancer[ 17 ]. Furthermore, m6A modification participates in the various aspects of tumor development, such as immunity, metabolism, and tumor stem cells’ self-renewal[ 18 , 19 ], emerging as an important molecular biomarker in tumor initiation and development. m6A dysregulation exerts multiple regulatory effects in GC[ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%